BRAND LOYALTY DITINJAU DARI BRAND EXPERIENCE, BRAND AUTHENTICITY DAN BRAND LOVE - ARYAN AGUS PRATAMA; IKA YULIANA; RESTU ALPIANSAH (Universitas Mahasaraswati K. Mataram, 2023)
The hotel and resort business are required to sustain consumer loyalty effectively. The study was carried out at Navotel Lombok Resort. The primary objective of this research is to ascertain the impact of brand experience, brand authenticity, and brand love on brand loyalty. Furthermore, this study aims to examine the potential mediating effects that may arise through the concept of brand love. The present study used a descriptive quantitative research design. The sampling approach employed in this study was purposive sampling. The present study discovered a noteworthy and affirmative relationship between brand authenticity and brand love, indicating that both factors substantially influence brand loyalty in contrast to brand experience, which has been found to have a limited impact on brand loyalty. Moreover, the impact of brand experience and authenticity on brand love is positive and substantial. The subsequent finding demonstrates an indirect relationship between brand experience and brand authenticity with brand loyalty, mediated by brand love.